KETAHANAN EKONOMI MASYARAKAT BALI AGAKECAMATAN BANJAR KABUPATEN BULELENG - Dharma Hartawan, I Gusti Made; Suyana Utama, I Made (Buletin Studi Ekonomi; VOL.23.NO.2.AGUSTUS 2018, 2019)
Economic Resilience of Bali Aga Community of Banjar Sub-district of Buleleng Regency. Bali aga community on economic activity shows that they have traditional knowledge, skills and technology in using resources to survive. Therefore, the economic activity based on togetherness and kinship in the midst of market dynamics that tend to be individualistic becomes important to be maintained, which is analyzed with the comparative descriptive approach, where the documents and interviews as data collection techniques. Any results obtained are the economic concept of Tri Hita Karana concept is achieved by inserting Hindu ethical values, such as Karma Yoga , Tri Kaya Parisuda , and Artha Sastra into production, distribution and consumption activities, through sustainable local institutional effectiveness.